2015
DOI: 10.1093/bja/aev317
|View full text |Cite
|
Sign up to set email alerts
|

Liberal transfusion strategy improves survival in perioperative but not in critically ill patients. A meta-analysis of randomised trials

Abstract: According to randomized published evidence, perioperative adult patients have an improved survival when receiving a liberal blood transfusion strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 44 publications
4
64
0
2
Order By: Relevance
“…Notably, a recent meta-analyses 63 confirmed that EBM is in favor of a liberal transfusion strategy in surgical patients, and the results of the TRICS III trial 64 will hopefully provide clearer insights about this topic.…”
Section: Implications For Clinical Practicementioning
confidence: 98%
“…Notably, a recent meta-analyses 63 confirmed that EBM is in favor of a liberal transfusion strategy in surgical patients, and the results of the TRICS III trial 64 will hopefully provide clearer insights about this topic.…”
Section: Implications For Clinical Practicementioning
confidence: 98%
“…Two recent systematic reviews in cardiac surgery [19] and in perioperative transfusion practice (including cardiac surgery) [20] reported higher mortality with a restrictive transfusion threshold. Our systematic review [21] found only 11 blood transfusion threshold randomized controlled trials (RCTs) that included patients with co-existing CVD, either as the whole population [10,[22][23][24], as a pre-defined subgroup [9,11,25] or as a high proportion of patients [14,[26][27][28].…”
Section: Evidence In Patients With Co-existing Cardiovascular Diseasementioning
confidence: 99%
“…The definitions of serious infections and health care-associated infections were not clear when comparing data from the included studies. 24 In 7,552 perioperative patients (17 RCTs), Fominskiy et al 26 found that a liberal blood transfusion strategy improved survival in acute anemia. The perioperative settings were hip fracture surgery, cardiac surgery, abdominal cancer surgery, elective hip and knee replacement, spinal fusion with instrumentation, and postpartum hemorrhage.…”
Section: Various Disease Groupsmentioning
confidence: 99%